Gender Equality in the Ivory Tower, and How Best to Achieve It. Issue 2 (14th April 2014) - Monroe, Kristen Renwick; Choi, Jenny; Howell, Emily; Lampros-Monroe, Chloe; Trejo, Crystal; Perez, Valentina
ABSTRACT Both statistical and qualitative interview data confirm the on-going existence of gender inequality within American academia, with women both underrepresented and underpaid compared to their male counterparts. Surprisingly, what is needed to remedy this situation is not a secret. Most of the policies outlined in this article as good workable solutions are programs that have been tested and described in more than one study. Indeed, evidence suggests that when the nine strategies we identify here are fully implemented, as they have been at a few colleges and universities, the number of women on the faculty increases dramatically. The fact that we do not adopt these policies more widely in academia suggests not a lack of knowledge so much as apathy, prejudice, gender stereotypes, and cultural cues that end by depriving society of some of its best talent and energy.